The Relationship between Leadership, Motivation, and Workload on Burnout with Resilience as a Mediator Variable in Government Employees in Genuk District - Sabrina, Farah Sabrina Azaranza; Sumastuti, Efriyani; Dharmaputra, M Fadjar (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to determine the relationship between leadership, motivation, and workload and burnout in government employees in Genuk District. As well as to find out whether resilience can be a mediator variable between independent variables and dependent variables. The research method used was quantitative by taking a sample of 100 respondents to government employees in Genuk District. Data collection was carried out using a questionnaire consisting of 5 dimensions, namely leadership, motivation, workload, and burnout. Where the leadership dimension consists of 8 items, the motivation dimension consists of 6 items, the workload dimension consists of 4 items, the resilience dimension consists of 10 items, and the burnout dimension consists of 6 items. Data analysis by applying JASP software using product moment correlation test, multiple correlation test, and sobel test. Where the analyzed test shows that there is a relationship between the leadership, motivation, and workload variables on the burnout variable with the mediated resilience variable having 2 stronger strengths.